Effect of ingesting a sports drink on soccer training intensity and performance - Tan, Beatrice Li Bin (2016)
Purpose: During exercise, soccer players are encouraged to consume sports drinks, which contain carbohydrate, to provide energy to the working muscles and central nervous system. While there is strong evidence to support the effectiveness of sports drinks on performance in competition, there is significantly less evidence available for performance during training.